The study of heat transfer intensification during boiling of a nanofluid on a heating surface with a nanorelief - E. N. Slobodina; A. G. Mikhailov; E. A. Rogachev; A. M. Paramonov; E. A. Gass (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The study of the boiling liquids processes is currently relevant, as it affects many energy areas and can offer new ways to improve the efficiency of energy plants. The properties and the nanolayer formation processes on the heater surface are the area of interest. Modification of the heater surface in power machinery with the formation of a porous layer on them is more promising than using nanofluid as a heat transfer fluid. The research of the nanolayer formation a during boiling provides insights into its properties and its effect on heat transfer during boiling. It has been experimentally established that when the suspension boils, porous deposits form on the heat exchange surface. Initially, the roughness caused by the deposition of nanoparticles increases, but after a while it begins to decrease due to the alignment of the sediment profile.